Selective spatial localization of actomyosin motor function by chemical surface patterning - Sundberg, Mark (Langmuir : the ACS journal of surfaces and colloids, 2006)
We have previously described the efficient guidance and unidirectional sliding of actin filaments along nanosized tracks with adsorbed heavy meromyosin (HMM; myosin II motor fragment). In those experiments, the tracks were functionalized with trimethylchlorosilane (TMCS) by chemical vapor deposition (CVD) and surrounded by hydrophilic areas. Here we first show, using in vitro motility assays on nonpatterned and micropatterned surfaces, that the quality of HMM function on CVD-TMCS is equivalent to that on standard nitrocellulose substrates. We further examine the influences of physical properties of different surfaces (glass, SiO(2), and TMCS) and chemical properties of the buffer solution on motility. With the presence of methylcellulose in the assay solution, there was HMM-induced actin filament sliding on both glass/SiO(2) and on TMCS, but the velocity was higher on TMCS. This difference in velocity increased with decreasing contact angles of the glass and SiO(2) surfaces in the range of 20-67 degrees (advancing contact angles for water droplets). The corresponding contact angle of CVD-TMCS was 81 degrees. In the absence of methylcellulose, there was high-quality motility on TMCS but no motility on glass/SiO(2). This observation was independent of the contact angle of the glass/SiO(2) surfaces and of HMM incubation concentrations (30-150 microg mL(-)(1)) and ionic strengths of the assay solution (20-50 mM). Complete motility selectivity between TMCS and SiO(2) was observed for both nonpatterned and for micro- and nanopatterned surfaces. Spectrophotometric analysis of HMM depletion during incubation, K/EDTA ATPase measurements, and total internal reflection fluorescence spectroscopy of HMM binding showed only minor differences in HMM surface densities between TMCS and SiO(2)/glass. Thus, the motility contrast between the two surface chemistries seems to be attributable to different modes of HMM binding with the hindrance of actin binding on SiO(2)/glass